PKCη deficiency improves lipid metabolism and atherosclerosis in apolipoprotein E‐deficient mice. (22nd August 2016) - Torisu, Kumiko; Zhang, Xueli; Nonaka, Mari; Kaji, Takahide; Tsuchimoto, Daisuke; Kajitani, Kosuke; Sakumi, Kunihiko; Torisu, Takehiro; Chida, Kazuhiro; Sueishi, Katsuo; Kubo, Michiaki; Hata, Jun; et al.
Abstract : Genomewide association studies have shown that a nonsynonymous single nucleotide polymorphism in PRKCH is associated with cerebral infarction and atherosclerosis‐related complications. We examined the role of PKCη in lipid metabolism and atherosclerosis using apolipoprotein E‐deficient ( Apoe −/− ) mice. PKCη expression was augmented in the aortas of mice with atherosclerosis and exclusively detected in MOMA2‐positive macrophages within atherosclerotic lesions. Prkch +/+ Apoe −/− and Prkch −/− Apoe −/− mice were fed a high‐fat diet (HFD), and the dyslipidemia observed in Prkch +/+ Apoe −/− mice was improved in Prkch −/− Apoe −/− mice, with a particular reduction in serum LDL cholesterol and phospholipids. Liver steatosis, which developed in Prkch +/+ Apoe −/− mice, was improved in Prkch −/− Apoe −/− mice, but glucose tolerance, adipose tissue and body weight, and blood pressure were unchanged. Consistent with improvements in LDL cholesterol, atherosclerotic lesions were decreased in HFD‐fed Prkch −/− Apoe −/− mice. Immunoreactivity against 3‐nitrotyrosine in atherosclerotic lesions was dramatically decreased in Prkch −/− Apoe −/− mice, accompanied by decreased necrosis and apoptosis in the lesions. ARG2 mRNA and protein levels were significantly increased in Prkch −/− Apoe −/− macrophages. These data show that PKCη deficiency improves dyslipidemia and reduces susceptibility to atherosclerosis in Apoe −/− mice, showing that PKCη plays a role in atherosclerosis development. Abstract : We found that the dyslipidemia observed in Prkch +/+ Apoe −/− mice was improved in Prkch −/− Apoe −/− mice. HFD‐induced liver steatosis was markedly attenuated in Prkch −/− Apoe −/− mice. Consistent with improvements of dyslipidemia, atherosclerotic lesions were decreased in HFD‐fed Prkch −/− Apoe −/− mice.